Brain Mapping of Low and High Implusivity based P300 Signals - Turnip, Arjon; Dwi, Esti K.; Hidayat, Taufik; Hidayat, Teddy (Journal of physics. Conference series, 2018)
Impulsiveness is defined as action without good planning and with little consideration the consequences. Impulsive actions are typically poorly conceived, prematurely expressed, or inappropriate to the undesirable situation such as abuse of drugs. Instead of taking treatment for an addiction subject, it is better take prevention. In this paper, an implusivity detection based EEG-P300 potential is proposed. Twenty four subjects consist of three groups (addiction, methadone, and control) are involved in the experiment. Five different pictures (one picture related drug is used as a target) were randomly flashed to the subjects. The subject is asked to comfortly sit in a chair and to silently count the appearance number of the target. The high amplitude of the P300 component with shortest latency and dominant brain activity are indicated by high implusive group.